Motion mechanism concept and morphology of a single actuator tetrapod walking spider robot: the ROBOTURK SA-2 Robot - Soyguder, Servet; Alli, Hasan (Emerald Group Publishing Ltd, 2011)
Purpose - This study seeks to develop a novel eight-legged robot. Additionally, this study defines design and control of an eight-legged single actuator walking ROBOTURK SA-2 spider robot based on the features of a creatural spider. Design/methodology/approach - First, the single actuator eight-legged tetrapod walking spider robot was modeled on solid works and then the animation of the model was realized to ensure the accurate walking patterns and more stable walking. Based on this model, the novel prototype of the single actuator eight-legged walking spider robot was constructed. Findings - A novel motion mechanism uses only one actuator for driving the system. Originality/value - The modeled single actuator eight-legged robot is original in terms of the developed motion mechanism.
Keywords: Robotics; Motion; Actuators